Analise e plano de melhorias para o modelo de gestão e organização de estoque em um almoxarifado de uma multinacional - GONÇALVES JÚNIOR, Wanderlei Ferreira (2019)
The present study aimed to propose a management model in a warehouse, with the support of mathematical methods for stock control and process improvement. The analysis was done primarily verbal and visual in the operational and administrative activities of the warehouse, after which a survey of all items in stock for quantitative and control knowledge was made. From that moment on, any products that went into or out of stock were controlled, in parallel to which a 5W1H action plan was formulated to implement the 5S philosophy, adding positive points to the control of the warehouse. With organized and controlled stock, the control worksheet was optimized, with resupply formulas and security stock, giving reliability when requesting the purchase of some item, and improving and consolidating communication with the purchasing sector, avoiding gaps in inventory, reducing losses and investing only the necessary, showing that the tools used were effective and fulfilled with the proposed objectives.